Proyecto de intervención sobre el desarrollo emocional para la integración-elaboración de vivencias internas y externas traumáticas por medio del juego en niños y adolescentes del centro de acogida Mi Caleta durante el periodo de abril a julio del 2018 - Achig Guerra, Dayana Paola (2019)
Children and adolescents in street situations experience strong emotional impacts because of family abandonment and social exclusion. These factors produce deterioration in the affective sphere and in the representation of themselves and the world that surrounds them. This deterioration causes a little adaptive action and without the personal resources necessary to face the demands of the social environment. From this perspective, the objective of the project was to contribute to the improvement of the emotional development of the Children and Adolescents of the Welcome Center “Mi Caleta” from 10 to 14 years old, through the game as a transactional space. This therapeutic tool was used with the purpose of integrating-elaborating high intensity emotions and traumatic experiences through individual and group activities that allowed placing all those situations of difficult assimilation in the psyche in a non-invasive and quite creative way. Therefore, through this work, the reader will know: How the project arose?, What was its importance and what lessons learned from it?, taking as a central point the impact that the intervention produced in the mental health of the Children and Adolescents of the Welcome Center "Mi Caleta" and how the game, from the clinical field, can be used for the expression, recognition and elaboration of emotions in populations with the same social, psychological and cultural characteristics.